SYSTEMATIC LITERATURE REVIEW: OBSTACLES AND STRATEGIES TO IMPROVE THE COMPETENCE OF PAI TEACHERS IN SENIOR HIGH SCHOOLS - Nur Adilah; Slamet Riyadi; Suwardi, Suwardi (Ikatan Dosen Menulis, 2024)
Islamic Religious Education (PAI) teachers often face obstacles, such as limited training, minimal access to technology-based resources, and high administrative burdens. This analysis aims to identify the main obstacles and provide strategies to improve the competence of PAI teachers in Senior High Schools (SMA). The analysis was conducted using the Systematic Literature Review [SLR] method with the PRISMA approach. A total of 25 relevant scientific articles from leading databases, such as Scopus, Google Scholar, and Web of Science, published between 2018–2024 were analyzed in depth. The results of the analysis show that the obstacles faced by PAI teachers are the lack of practice-based training, limited digital learning resources, and low institutional support in adopting modern technology. Strategies that have proven effective in overcoming these obstacles include the development of practice-based training programs, the use of digital learning media, and the formation of learning communities to improve collaboration between teachers. Improving the competence of PAI teachers has a significant positive impact, such as increased student engagement in learning, stronger internalization of Islamic values, and the adoption of innovative learning methods that are relevant to student needs. This analysis provides an important contribution in designing policies and programs to improve the competence of Islamic Religious Education teachers that focus on technology integration and professional collaboration. The implications of these findings can support education providers in creating a sustainable and more effective learning ecosystem, so that it can improve the quality of Islamic Religious Education learning at the high school level and have a positive impact on the formation of student character.